Skeletal muscle tissue engineering - Schäfer, Benedikt; Cai, Aijia; Ruhl, Tim; Beier, Justus P. (Tissue Engineering Using Ceramics and Polymers, 2021)
The largest tissue mass in the human body consists of skeletal muscle. It is essential for posture and motion. Different causes are responsible for a critical volume loss of skeletal muscle, e.g., traumatic injury or tumor ablation. This leads to consequences, such as pain, deformity, loss of function, and joint malfunction. The regenerative capacity of skeletal muscle is very low, due to the limited proliferative capability of adult muscle stem cells, the so-called satellite cells. Therefore, mesenchymal stem cells are promising cell alternatives for skeletal muscle tissue engineering, because they can be easily harvested in high numbers from the bone marrow or adipose tissue and differentiated into various cells of the mesodermal lineage, including muscle cells. In a clinical setting, muscle tissue can only be replaced by sacrificing other muscle tissue. Thus, the engineering of artificial and functional skeletal muscle tissue is of interest in biomedical research. The extracellular matrix (ECM) of the skeletal muscle differs from the ECM of other tissues. The special requirements for elasticity and yet high strength represent a specialty in skeletal muscle tissue engineering, which could be achieved by using artificially constructed nanofibers as a growing matrix for muscle precursor cells. In this chapter, we review the application of different polymers for muscle tissue engineering. The use of nanofibers in tissue engineering seems promising because they offer large surfaces for cell attachment to support optimal cell interactions and development. Furthermore, polymers supplemented with conductive and bioactive substances, or mechanically improved structures are used as scaffolds to mimic the natural ECM of skeletal muscle to facilitate cellular development.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 3-D scaffolds; Mesenchymal stem cells; Nanofibers; Polymers; Satellite cells; Skeletal muscle tissue engineering